Dados abertos conectados a partir de catálogos online de bibliotecas - Vanessa Marta de Jesus (2021)
Over the years, advances have been developed for the exchange of information between bibliographic records that make up online library catalogs, such as the creation of the Z39.50 protocol and the Open Archives Initiative - Protocol for Metadata Harvesting (OAIPMH) and the MARC format, which binds the registration exchange. In this scenario, it becomes possible to import data and reuse records from other libraries, in a collaborative way, reducing costs and rework in the cataloging process. A new possibility for incremental innovation in the library scenario is open data, the main focus of this master's research, whose research environment is the online library catalogs. Connected data can be understood as a set of nodes, which comprises a union of various data and links which can be considered as known. Its standards allow the publication of data in such a way that it can be read by people and processed by machines. They make it possible for the institution's collection to be accessible to anyone through interoperability, contributing to different systems selected on the Web to search for information. The current library catalogs have limitations considering the Web context. In this scenario, the general objective of this research is to map the challenges found in the implementation of available data practices connected in libraries to make their catalogs available online on the Web. As a methodology, the research is characterized as applied and exploratory, using bibliographical and documentary research. The research technique adopted is Bardin's content analysis, comprising the phases of elaboration of records for initial analysis of the texts, creation of categories for data categorization, grouping of data in the categories created and analysis and interpretation of data. As a result, it was found that the challenges achieved refer to the metadata format, licenses, provenance and quality, identifiers, formats, vocabularies, access, preservation, data enrichment. The barriers observed were related to scarce financial resources, lack of qualified human resources, low level of awareness among the community/librarians and dependence on the foreign market for software acquisition. It is concluded that technology is not the main obstacle for publishing connected data from library catalogs, although changing the current metadata model adopted is not an easy task and there are many challenges to overcome. It was observed, however, that the challenges exist not for lack of requirements, but for the complexity involved in the process of publishing open data connected from online catalogs, combined with the lack of qualified personnel to perform the function, the scarcity of financial resources and the need to raise awareness among staff about the benefits arising from the adoption of open data connected by libraries.